2020
DOI: 10.3762/bjoc.16.118
|View full text |Cite
|
Sign up to set email alerts
|

An overview on disulfide-catalyzed and -cocatalyzed photoreactions

Abstract: Disulfides are versatile catalysts. They can be photocatalysts, hydrogen atom transfer (HAT) catalysts, cocatalysts, or initiators in photocatalytic reactions. Under photoirradiation, organic disulfides can be easily cleaved into free thiyl radicals (RS•) and can reversibly add to unsaturated multiple bonds to catalyze a variety of functionalization reactions under mild conditions. In photoredox catalysis reactions, an excellent electron transfer ability and excellent radical properties also made these thiyl r… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
23
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 39 publications
(29 citation statements)
references
References 33 publications
1
23
0
Order By: Relevance
“…The D-incorporation was significantly improved (92% D-inc.) by replacing the thiol with dimethyl disulfide (entry 13). The higher reaction efficiency might be attributed to the fact that in contrast to the thiols, organic disulfides can be easily cleaved into free thiyl radicals useful in the deuterium transfer without introduction of additional protons 64 . Photocatalysts PC2 – PC4 could be used in the reaction, while gave reduced yields or/and deuterium incorporation (entries 16–18).…”
Section: Resultsmentioning
confidence: 99%
“…The D-incorporation was significantly improved (92% D-inc.) by replacing the thiol with dimethyl disulfide (entry 13). The higher reaction efficiency might be attributed to the fact that in contrast to the thiols, organic disulfides can be easily cleaved into free thiyl radicals useful in the deuterium transfer without introduction of additional protons 64 . Photocatalysts PC2 – PC4 could be used in the reaction, while gave reduced yields or/and deuterium incorporation (entries 16–18).…”
Section: Resultsmentioning
confidence: 99%
“…In addition, PS-A promoted the oxidation of styrene 4 to benzaldehyde 2a , and the further reaction of PS-A with the in situ-formed 2a generated 3a in 70% yield. Wang reported that sulfides with electron-rich aryl substituents showed better reactivity as a PS . Considering such reactivity, PS-A bearing the electron-rich aniline moiety could be a good PS.…”
Section: Resultsmentioning
confidence: 99%
“…Previously, Wang and co-workers successfully demonstrated the use of disulfides as photosensitizers for oxidative cleavage of styrene derivatives (Scheme b) . Inspired by this work, we proposed that if disulfide is in equilibrium with the starting 2-aminothiophenol, the benzothiazole synthesis would proceed in the presence of visible light and a molecular oxygen atmosphere without the need for an external PS.…”
Section: Introductionmentioning
confidence: 98%
“…In visible-light photocatalysis, thiolates are readily oxidized by an excited photoredox catalyst to generate thiyl radicals, which are employed for the construction of organosulfur molecules, and used as hydrogen atom transfer agents (Scheme A,B) . Additionally, thiyl radicals are produced from photolysis of disulfides, which have been utilized in a variety of chemical transformations in a catalytic manner (Scheme C). , Excited sulfur-based anions are potent electron donors as a photocatalyst and can be used for inert bond activation. Moreover, upon photoinduced electron transfer between sulfur anions and substrates, the resulting sulfur-centered radicals and substrate radical anions are valuable intermediates in subsequent reaction steps.…”
Section: Introductionmentioning
confidence: 99%
“…11 Additionally, thiyl radicals are produced from photolysis of disulfides, which have been utilized in a variety of chemical transformations in a catalytic manner (Scheme 1C). 12,13 Excited sulfur-based anions are potent electron donors as a photocatalyst and can be used for inert bond activation. Moreover, upon photoinduced electron transfer between sulfur anions and substrates, the resulting sulfur-centered radicals and substrate radical anions are valuable intermediates in subsequent reaction steps.…”
Section: Introductionmentioning
confidence: 99%